Experimental and Numerical Acoustoelectric Investigation of the New SAW Structure with (RR)-P3HT Polymer in DMMP Detection - Tomasz Robert HEJCZYK; Jarosław WROTNIAK; Mirosław MAGNUSKI; Wiesław JAKUBIK (Archives of Acoustics, 2021)
This document presents the results of numerical analyses of the SAW gas sensor in the steady state. The effect of SAW velocity changes depending on how the surface electrical conductivity of the sensing layer is predicted. The conductivity of roughness sensing layer above the piezoelectric waveguide depends on the profile of the diffused gas molecule concentration inside the layer.